A time-series based framework for exploring the unknown effects of shoe comfort-induced biomechanical adaptations - Rodrigo-Carranza, V.; González-Mohíno, F.; Casado, A.; Santos-Concejero, J.; Galán-Rioja, M. A.; González-Ravé, J. M. (Footwear Science, 2023)
Critical speed represents the highest exercise intensity at which the oxidative phosphorylation is sufficient to satisfy the energy demand. Since the release of the advanced footwear technology in May 2017, every road record from the 5-km event to the marathon has been broken. The question arises whether this type of footwear improves critical speed and, thus, performance. The aims of this study were (i) to assess the impact of advanced footwear technology on critical speed and D' (curvature constant of speed-time relationship) in male elite distance runners, and (ii) to analyse the interference of the weather conditions and orography on such influence. Critical speed and D' were calculated using the linear distance-time model analysis in eleven runners through their season best performances in two distance running events (10-km and half-marathon) during the same season. Six runners were wearing advanced footwear technology during the advanced footwear technology era and not wearing this footwear during the pre-advanced footwear technology era (experimental group), and five runners were not wearing advanced footwear technology during any of both eras (control group). Critical speed improved by 3.31% in the experimental group when runners were wearing advanced footwear technology (p = 0.034; ES = 0.623), while in the control group did not change (p = 0.311; ES = 0.251). D' remained unchanged in both groups. Weather conditions and orography remained unchanged. The use of advanced footwear technology resulted into an improved critical speed which could explain the improvement in performance with this type of footwear in recent years in elite runners.